International Youth Camp: Empowering Diversity in Education - Fauziyyah, Gesha Lailatul; Sulaeman, Dedi; Masitoh, Siti (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2025)
This study aims to discuss the International Youth Camp Program as a way to empower diversity in the educational field. Since empowering diversity among learners would bring a positive education atmosphere, such empowerment is essential for learners to adapt and embrace differences found in the classroom. This study used a qualitative method with research data collected from interviews and observation, involving 21 students from 13 countries attending the International Youth Camp in a private university in West Java. The interview results showed that the International Youth Camp helped students of different cultures and languages exchange ideas. Furthermore, the observation results imply that this event has successfully promoted diversity for both Indonesian and international students by introducing their cultures to each other. This program also provides opportunities for both Indonesian and international students to exchange and collaborate on their knowledge, language, culture, and character development. Therefore, this program contributes to the field of intercultural education by offering empirical evidence on how international youth programs can serve as effective platforms for fostering global citizenship, promoting inclusive values, and developing students’ intercultural competence. It underscores the significance of experiential, dialogue-based learning in enhancing students’ openness, adaptability, and respect for diversity in higher education settings.